Effect of promotion cost on sales value carica fruit based products (case study at Yuasafood Berkah Makmur Wonosobo) - Wijayanto, Khusaini Wijayanto (PHINISI, 2023)
A carica fruit processing industry called UD. Yuasafood Berkah Makmur is located on Dieng Street km. 3.5, Krasak Village, Mojotengah District, Wonosobo Regency, Central Java. This study aims to determine if UD. Yuasafood Berkah Makmur's promotion expenses have a real and substantial impact on the sales value of carica fruit goods. The Annual Report statistics for the years 2007 through 2011 were used in this study. Simple linear regression analysis, the t test, coefficient of determination (R2), and the F test were used to examine the data. Promotion cost (X) served as the study's independent variable, and sales value served as the study's dependent variable (Y). The SPSS (Statistical Package for Social Science) software and manual calculations were used to process the two variables. Using a variety of statistical test analyses, including simple linear regression analysis, the t test, analysis of the coefficient of determination (R2), and the F test.